Pemanfaatan Sereh Wangi Sebagai Lilin Aromaterapi - Kristina Tresia Leto; Nursina Sya’bania; Kartini Rahman Nisa; Sunarwin Sunarwin; Germanus Gleko (Universitas Pendidikan Muhammadiyah Sorong, 2022)
A maximum 200 word abstract in English in italics with Times New Roman 11 points. The abstract should be clear, descriptive, and should provide a brief overview of the problem studied. Abstract topics include reasons for the selection or the importance of research topics, research methods, and a summary of the results. The abstract should end with a comment about the importance of the results or a conclusions brief. Dengue is a very serious disease as it causes a fairly high mortality rate. In Sikka Regency, dengue cases have frequently been categorized as Extraordinary Events. Various efforts have been conducted to overcome the cases. However, many local people have not been aware of both the dangers and solutions to overcome the cases. An alternative solution offered is the use of aromatherapy candles as a mosquito repellent. Aromatherapy candles which are made from citronella (widely grown in local people's yards) can be used as an alternative to repel mosquitoes or eradicate larvae. This community service activity was carried out by providing counseling related to the dangers of dengue and aromatherapy candles making as an alternative solution to repel mosquitoes. In addition to counseling, training was also provided in the manufacture of aromatherapy candles. It is hoped that local people are increasingly aware of the dangers of dengue and can make use of the plants around their neighborhood.